Participation in self-help groups and empowerment among rural women in Niger State, Nigeria - Ndaeji, Muhammad Ndas (2014)
In Nigeria like many other developing countries, women’s access to positions of influence, power and resources is restricted. Therefore, the widespread formation of self help groups among Nigerian rural women in agricultural activities as a strategy for women empowerment have arisen out of the perceived problem of women’s lack of access to resources and high level of poverty among women. Thus, the general objective of this study was to explore to what extent does women participation in Self Help Groups (SHGs) on agricultural activities by Niger State rural women empower the members. The study also aimed to examine the linkages among volunteerism, participation and empowerment (social, economic and psychological) in SHG practice. The study utilized three theoretical approaches in this study (volunteerism, participation and empowerment) as well as examining relevant studies conducted in the area being study. The study measured three types of women’s needs (social, economic and psychological) that might have influenced their volunteerism and participation in SHG programmes. In addition, the study also measured three types of women’s empowerment (social, economic and psychological). Women’s level of participation in group activities, their types of participation and level of their volunteerism towards the activities of the group programmes were also examined to understand their degree and forms of involvement. Data were collected from thirty women’s SHGs comprising a total population of 712. The sample size of 282 was randomly selected to participate. The study employed the survey method with self- administered questionnaire to answer several questions about women’s needs, women’s empowerment, participation and volunteerism. Informal interview was used to support the collection of information from the key informants of SHGs.Data were analyzed using descriptive statistic, correlation analysis and regression coefficients analysis. The findings showed that the level of women’s empowerment is moderate among the rural women of SHGs. Among the socio-economic status variables such as age, educational qualification, occupation of members and their husbands, number of their children and family income has significant relationship with women’s empowerment. The Pearson correlation analysis showed that there was a high positive relationship between the level of women’s participation and the three dimension of women empowerment (social, economic and psychological).The Pearson correlation analysis showed that there was a low statistical significant positive correlation between women’s need (social, economic and psychological) and women’s empowerment (social, economic and psychological). The regression coefficients analysis indicated that there was high significant contribution of level of participation to the process of women’s empowerment (social, economic and psychological). The hierarchical regression analysis conducted also showed moderate significant relationship among volunteerism, participation and empowerment. The overall finding showed that with a high spirit of volunteerism and active participation within individual and groups in SHGs, the success of building a group, community and society will be fully attainable. The findings of this study would enrich the body of literature on women empowerment and community development. The present study advances the contribution of SHG understanding to women empowerment in Niger State. Finally, stemming from the findings of this research, the study proposed a number of recommendations that are directed toward enhancing women’s empowerment strategies through the group approach of SHGs. These include the formulation and institution of a common policy by the government for SHGs which will help better coordinate their activities and promote effective collaboration among groups. The study also proposed that government should intervene through people’s banks, community banks and other micri-finance institutions in the area of granting credit to groups with low interest rate.